Design and flow analysis of a vertical axis wind turbine by using ceiling fan as generator. (2022) - Edwin Joseph, R.; Paranthaman, V.; Shanmuganandam, K.; Natrayan, L.
Abstract: A Vertical Axis Wind Turbine is one among the types of the turbine which runs through Wind power. The turbine which is designed for the project comes under the type Darreus Rotor, this particular type has low drag value compared to Savonius type which has higher drag and low lift force. The Vertical Axis Wind Turbine which is fabricated can be used in city areas depending on the average Wind condition in that area. We have chosen our college to be suitable place where we can install the turbine and get expected outputs due to the continuous flow of wind across the buildings. The turbine which is fabricated and designed is small and home sized turbine. The turbine is coupled with a ceiling fan generator which is replaced with Neodymium Magnets around the periphery of the rotor. This will provide the necessary magnetic field to produce EMF across the coils. The further output of the system can be given to low voltage battery pack to store the power.